How things work : discover secrets and science behind medieval machines, jet packs, movie magic, and everything in between - Resler, Tamara J. (National Geographic kids., 2018)
Explores facts about how machines and technology work. Topics range from ancient computers and underwater archeology to animatronics and animation. Includes text-related activities, step-by-step instructions, a glossary, and color photographs.